THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN MODERATING THE EFFECT OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON FIRM VALUE IN INDUSTRIAL COMPANIES - Rifqi, Muh.; Bakry, Mohammad Iqbal; Parwati, Ni Made Suwitri; Masruddin, Masruddin (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstrak This study aims to analyze the influence of profitability, liquidity, and leverage on company value and to test the role of Corporate Social Responsibility (CSR) as a moderating variable. The research subjects were industrial sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The study employed a quantitative approach with secondary data obtained from financial statements, annual reports, and corporate sustainability reports. The sampling technique employed a purposive sampling method, resulting in 17 companies with a total of 68 observations. Data analysis was performed using Partial Least Square-based Structural Equation Modeling with the assistance of WarpPLS 8.0 software. The results showed that profitability, liquidity, and leverage had a positive and significant effect on financial performance. Meanwhile, Corporate Social Responsibility was unable to moderate the relationship between profitability, liquidity, and leverage on financial performance. The findings of this study indicate that the financial performance of industrial sector companies is more influenced by internal financial performance factors than by the level of corporate social responsibility disclosure. Keywords: profitability, liquidity, leverage, corporate social responsibility, financial performance.